Contestation to the European Union on nuclear non-proliferation - Herrera, M. (Global Affairs, 2021)
This article analyses the contestation of the European Union’s (EU) nuclear non-proliferation policy. Contestation is as a social practice by which third actors express in discursive or practical terms their disapproval of certain norms and the actions that match them. In this way, norms are challenged, reinterpreted and transformed; and as a consequence, the validity of the norms is weakened or reinforced. There are reasons to believe that, as it is happening in other areas of EU foreign policy, the Union’s role in the global nuclear non-proliferation regime is becoming increasingly controversial. The article argues that the contestation to the EU’s nuclear non-proliferation policy is the result of its actions and positions in both in multilateral (i.e. The Non-Proliferation Treaty Review Conference), and bilateral (i.e. EU-India relations) settings.